PENGEMBANGAN MEDIA PEMBELAJARAN "MITIGAKSI SEKARANG!" BERBASIS ROBLOX UNTUK MITIGASI BENCANA SISWA SMA SAMARINDA - Riezky Jayanie, Aisyah; Vita Romadon Ningrum, Mei; Azmi, Nurul; Sekar Kedhaton, Arum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The high risk of disasters in Samarinda City necessitates the development of innovative and interactive disaster mitigation learning media for students. This study aims to develop a Roblox-based disaster mitigation educational game ent itled "MitigAksi Sekarang!" for Grade XI senior high school students in Samarinda City, assess its feasibility, and examine user responses toward the developed media. This study employed a Research and Development (R&D) method using the ADDIE development model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects comprised 3 students in the small group trial, 10 students in the medium group trial, and 30 students in the large group trial. The content expert validation yielded a percentage of 94.53% and the media expert validation obtained 98.86%, both categorized as Very Feasible. Teacher and student responses across all trial stages were categorized as Very Good. The N-Gain analysis revealed an average score of 0,3725, categorized as Moderate, indicating an improvement in students' understanding of disaster mitigation material after using the media. Therefore, the Roblox-based disaster mitigation educational game is declared feasible and effective for use in geography learning at the senior high school level.